The place of the Poznań stronghold and its significance for Wielkopolska and the Piast realm emerging in the 10th and the first half - Danielewski, Marcin (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2025)
The aim of the study is to present the role of the stronghold on Ostrów Tumski island in Poznań from the 10th to the mid-11th century. A key aspect of the considerations shown in the article remains the location of the feature in the changing structure of the Piast rule. Therefore, an attempt has been made to juxtapose Poznań with other central strongholds in Wielkopolska, namely Giecz, Grzybowo, Gniezno, Moraczewo, and Ostrów Lednicki. The paper discusses the origins of the stronghold on Ostrów Tumski but also focuses on the subsequent phases of its development. It is evident that the reign of Mieszko I remained crucial for Poznań, when the location underwent a major expansion to a four-part form, but above all was associated with the religious conversion. At that time, a palace with a chapel was built on Ostrów Tumski, accompanied by the construction of a cathedral for the first bishopric in the Polish lands, headed by Bishop Jordan. The Poznań stronghold did not diminish in importance during the reign of Bolesław I the Brave, and even though the ruler made Gniezno the capital of the archbishopric and a place of pilgrimage, Ostrów Tumski, located between the Warta and Cybina rivers, continued to be a key stronghold in the Piast realm. Poznań was a location for the peace negotiations in 1005, but also most likely the burial place of the rulers of the Piast dynasty.